(untitled) - NANIK ANDRIANI, DESY (LATERNE, 2014)
This research begins from students problem at MAN 2 Bojonegoro who have difficulty in writing a personal letter of the German language. The purpose of this research is to determine the learning results of students in the learning process of writing a personal letter to the German cooperative learning method Team Assisted Individualization (TAI) at XI Language grade MAN 2 Bojonegoro. This research is descriptive qualitative. This research is a test instrument. Data collection technique used was test of student learning results. The subjects were 29 students of XI Language grade MAN 2 Bojonegoro. Then the data were analyzed using appropriate assessment and described. After TAI applied learning method, student learning results obtained with a range of 78 to 97 and the value of the average value of 89,4. It can be concluded that the application of cooperative learning method Team Assisted Individualization (TAI) can give a good contribution to the learning results of personal letter writing skills German language students of XI Language grade MAN 2 Bojonegoro . Keyword: Team Assisted Individualization (TAI), Writing, Personal Letter